THE ROLE OF INFORMATION TECHNOLOGIES IN MODERN SOCIETY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines how information technologies (IT) have significantly transformed modern society. It focuses on the major sectors impacted by IT, such as communication, education, healthcare, business, and everyday living. The discussion also stresses the need for equitable and responsible use of technology so that its advantages reach all members of society. By analyzing current developments and real-world applications, the article offers a clearer understanding of how IT continues to drive greater connectivity, innovation, and efficiency in today’s world.